ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS GAME EDUKASI PADA MATA PELAJARAN MATEMATIKA SEKOLAH DASAR - Cahyati Hasanah, Ayu; Shokib Rondli, Wawan; Darmuki, Agus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this research is to analyze the use of educational game-based learning media in mathematics subjects in elementary schools, especially in SD 2 Bulungcangkring. The approach used in this research is a qualitative approach. The method used in this research is the case study method because this event or phenomenon occurred at SD 2 Bulungcangkring. The data collection techniques used in this research were observation, interview, and documentation. The subjects in this study were 15 people consisting of 6 class teachers and 9 students of SD 2 Bulungcangkring. The data analysis used three stages, namely data reduction, data presentation, and conclusions. The result of the research is that most teachers at SD 2 Bulungcangkring still teach math conventionally. However, there are some teachers who use educational game-based learning media in learning math. The use of educational games in math subjects creates math learning to be more interesting and fun and with the use of educational games can improve cognitive abilities and student learning outcomes at SD 2 Bulungcangkring. So it can be concluded that the use of educational game-based learning media in math subjects has a positive impact at SD 2 Bulungcangkring. Keywords: educational game, learning media, mathematics